Abciximab-Induced Thrombocytopenia: Correct Management - Kelkitli, E.; Odabaşi Giden, A.; Denız Kürekçi, D.; Turgut, M. (Ondokuz Mayis University, 2022)
Thrombocytopenia is a possible side effect of routinely administered medical agents. Abciximab is one of the three potent intravenous glycoprotein IIb/IIIa receptor inhibitors (along with eptifibatide and tirofiban) that have shown significant positive outcomes when used in patients with intracoronary thrombus. The use of abciximab was associated with the risk of thrombocytopenia. This case reported the development of thrombocytopenia and treatment management after using abciximab. © 2022 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Abciximab; Glycoprotein IIb/IIIa Receptor Inhibitors; Side Effect; Thrombocytopenia